Paideía and Sophía in the itinerary of the soul towards God: Abraham, Sarah and Hagar in the philonic exegesis (Circe de clásicos y modernos, 2018)
According to Philo, one of the approaches to virtue in the itinerary of the soul towards God is through what he considers the two most important levels of knowledge: education (παιδεία) and wisdom (σοφία). In this article we shall analyze the special features of the different stages in the apprentice’s journey towards wisdom by means of education, i.e. the spiritual union of Abraham (the intellect) and Sarah (virtue, wisdom), through his temporary mating with Hagar (the preliminary studies, education). Finally, we shall examine which is the role of divine intervention in this itinerary.
Keywords: education; wisdom; virtue; knowledge